Introduction - Holm Sophie; Wolff Charlotta (Germany, 2025)
Introduction [to Section 9: Philosophical Diplomats, Enlightened Physicians and Learned Merchants - Multiple Roles and Competing Practices in Eighteenth Century Scandinavia]